Factores socio-culturales influyentes para la aceptación del parto vertical implementado en el Hospital de Saraguro - Jaya Armijos, Olga Beatriz (2014)
Delivery care culturally comprises a set of attitudes actions aimed at increasing the access of communities, peoples, indigenous to institutional care, according to their customs. According to (WHO), in 2010 the global maternal mortality was 400 per 100,000 live births, revealing lack of health care stocks in 2010, Ecuador reported a maternal mortality rate of 161 deaths, knowing this problem that threatens the binomial mother-child, are interest with this study of descriptive and interpretative entitled influential vertical delivery acceptance implemented in Saraguro Hospital, the results of socio-cultural factors have been derived intervention plan that includes activities for promoting vertical delivery in the community with the largest indigenous population, the type of study was descriptive and interpretive, the study area was the Saraguro Base Hospital, the universe and sample consisted of 150 women. The technique used was the structured survey. The study found that 20.8% of indigenous women in labor suffer criticism for their poor hygiene practices, adding to this the 22.6% of indigenous mothers gestation period, have no knowledge of the implementation of the vertical delivery room at the Hospital of Saraguro With regard to the most accepted method by mestizo and indigenous mothers have to he 45.8% of the Western mothers use indigenous labor to give birth to their children, an important element in the indigenous culture, is the coat / dress is according to the study is 58.3% of indigenous mothers in labor, prefer to use their own clothing. 56.3% of indigenous women prefer to give birth is attended by a midwife. In traditional medicine used during labor by the midwife in the delivery room vertically with respect to indigenous mothers, 50% used the basil infusion and only 18.8% used the rough, in addition TBAs used infusion Pimpinela and macerated valerian to reduce anxiety and nerves at the time of delivery. Canchalagua. Parsley contributing to increase the body temperature of the mother, Melissa, to help the mother to open the bones finally the intervention plan was executed.